EFFECTIVENESS IN THE CURVE OF EIGHT TYPES OF ENDOSONIC TIPS FOR BROKEN INSTRUMENTS REMOVAL. - Kalin K. Shiyakov; Radosveta I. Vasileva (Peytchinski Publishing, 2014)
The aim of the study was to compare the effectiveness of eight endodontic ultrasonic tips in removing stainless steel fragments from the curve of simulated root canals. Methods: Each of the instruments - K-files 25 (EMS), ET25 (Satelec), Redo2 (VDW), RT3 (EMS), CPR8 (Obtura Spartan), Proultra8 (Maillefer), E7 (NSK) and ENDO E3 (W&H) was used to remove 10 stainless steel fragments from the curve of simulated root canals (Dentsply-Maillefer) under magnification 10x and 16x with a dental microscope (OPMI Pico, Carl Zeiss). Success rate, working time and root canal enlargement were recorded and compared. Results: Success rates were as follows: K-files - 80%, ET25 - 90%, Redo 2 - 80%, CPR8 - 70%, Proultra8 - 80%, RT3 - 70%, Endo E3 - 60%, E7 - 50%. The differences were not statistically significant. Working time - mean values: K-files - 8,44 min, ET25 - 9,28 min, Redo 2 - 9,53, CPR8 - 11,01 min, Proultra8 - 10,31 min, RT3 - 11,57 min, Endo E3 - 15,34 min, E7 - 21,45 min. Endo E3 and E7 showed significantly longer working time, the differences between the other tips were not significant. Mean values of canal diameters were - K-files - 1,11 mm, ET25 - 1,29 mm, Redo 2 - 1,31 mm, CPR8 - 1,54 mm, Proultra8 - 1,51 mm, RT3 - 1,61 mm Endo E3 - 1,68 mm and E7 - 1,72 mm. The differences in canal enlargement between CPR8, Proultra8, RT3, Endo E3 and E7 were not statistically significant. Conclusion: Endodontic ultrasonic tips with smaller diameters and sharp working points worked faster and preserved root canal better.